Fitness enhances psychosocial well‐being and self‐confidence in young men with hemophilia: Results from Project GYM. Issue 8 (26th November 2021) - Khair, Kate; Holland, Mike; Dodgson, Sandra; McLaughlin, Paul; Fletcher, Simon; Christie, Deborah
Abstract: Introduction: Contemporary hemophilia care supports physical activity, its benefits being well recognized. Despite recognition of the psychological challenges encountered by people with hemophilia, little is known about the psychological impact of physical fitness in this population. Aim: To identify changes in psychological well‐being in young men with hemophilia through participation in a gym program. Methods: This observational feasibility study of a 6‐month gym participation program used validated questionnaires pre‐ and poststudy to evaluate motivation to exercise, physical activity levels, self‐efficacy, self‐esteem, and quality of life. Individual audio‐recorded interviews about study participation and impact were transcribed verbatim and analyzed for recurring themes using thematic analysis. Results: Nineteen participants aged 18–25 years with hemophilia A or B (all severities ± inhibitor) consented to the study; two were lost to follow‐up. There was a shift in motivation to exercise as shown by the Stages of Change grouping moving from contemplation to action and maintenance phases ( p  = 0.03). Self‐efficacy overall scores showed a trend ( p  < 0.06) towards improvement. Median self‐esteem scores improved from 22 (range 12–30, n  = 19) to 25 (range 13–30, n  = 17), a statistically significant change ( p  = 0.02). Three participants recorded scores below the accepted normal range before study, of whom two improved at study end. The key themes identified from the interviews were: fear, self‐confidence, "being normal, " pain, weight loss, ability, getting fitter. Conclusions: The psychological wellbeing of young men with hemophilia improved during this study. This may have been related to participating in a gym‐based, physical exercise program.